Do the center of mass strategies change with restricted vision during the sit-to-stand task? - Aylar, Mozhgan Faraji; Dionisio, Valdeci Carlos; Jafarnezhadgero, AmirAli (Clinical Biomechanics, 2019)
Abstract Background The relationship between the visual sensory and center-of-mass characteristics during the sit-to-stand task is not well documented. Do the center of mass strategies change with restricted vision during the sit-to-stand task? Methods The participants in this study were fifteen girls with congenital blindness (age (94.6 (5.6) months), mass (25.6 (2.0) kg), and height (1.3 (0.0) m)) and 30 healthy girls with no visual impairment who were divided randomly into two groups. The two experimental condition groups consisted of one in which the participants were assigned to keep their eyes open (age (95.8 (5.4) months), by mass (26.1 (5.1) kg), and by height (1.3 (0.0) m)) and the other in which the participants were assigned to keep their eyes closed (age (93.8 (0.0) months), by mass (24.2 (0.0) kg), and by height (1.1 (0.0) m)) for 20 min before the test. The center-of-mass displacement of the foot, leg, and thigh were calculated for dominance and non-dominance during the sit-to-stand performance at initiation, seat-off, and end events. Findings Congenital blindness was associated with the non-dominant center-of-mass displacement of the foot increasing upwards during all events (initiation, p = 0.025; seat-off, p = 0.036; end, p = 0.034), as well the non-dominant center of mass of the foot moving anteriorly during the initiation point (p = 0.016). In addition, the center-of-mass displacements for the dominant and non-dominant feet (initiation, p = 0.006, and p = 0.016; seat-off, p = 0.006, and p = 0.014; end, p = 0.006, and p = 0.013, respectively) and legs (16.98%, p = 0.024, d = 0.95; and 17.88%, p = 0.032, d = 0.99, respectively) in the eyes-closed group shifted to a forward direction, and the center of mass of the non-dominant foot (initiation, p = 0.024; seat-off, p = 0.021; end, p = 0.012) moved significantly upwards. Furthermore, the whole body center of the mass velocity (anterior-posterior axis (initiation, p = 0.042; seat-off, p = 0.006; end, p = 0.005)) in the eyes-closed group was smaller than that in the eyes-open group. Interpretation The findings show that the sit-to-stand center of the mass components in blind children may have clinical importance for the rehabilitation of these subjects. Highlights • Visual memory could alter only some of center of mass components. • Adaptation of congenitally blind children can cause falls to achieve postural tasks. • 20-min with eyes closed can predispose to falling in a forward direction. • 20-min with eyes closed provokes worse balance control than the congenital blind.